Comparison of ELM-Filament Mitigation Between Supersonic Molecular Beam Injection and Pellet Injection on HL-2A - 聂林 程钧 徐红兵 黄渊 严龙文 丁玄同 许敏 许宇鸿 姚良骅 冯北滨 朱根良 刘万东 董家齐 余德良 钟武律 高金明 陈程远 杨青巍 段旭如 (Plasma science & technology, 2016)
On HL-2A,two different injections（supersonic molecular beam injection（SMBI）and pellet injection（PI）） are used to mitigate edge localized mode（ELM）-filament convective transport.The changes of their characteristics are studied in this paper.A high spatiotemporal resolution probe shows there are many similar phenomena,and the filament density amplitude and radial velocity are both suppressed.Our statistical results indicate that：the velocity suppression comes from the decrease of filament density and temperature;the transient particle and heat fluxes drop strongly;and long-range correlation along a magnetic flux surface also decreases,when the electron-ion collisionality increases significantly,which may have a role on the filament parallel current during ELM mitigation.